KAJIAN KELAYAKAN USAHA BUMDES BERDASARKAN ASPEK FINANSIAL DAN ANALISIS SENSITIVITAS (Studi Kasus BUMDes Usaha Kompos di Kecamatan Tebing Tinggi - Sofyan Marsyahadi; Bagus Pramusintho; Afriani H (Jurnal Riset Multidisiplin Edukasi, 2025)
Financial Feasibility Analysis of a Business is essential to determine an investment plan by comparing the costs incurred with the benefits obtained. This assessment includes the availability of funds, cost of capital, the business’s ability to repay the investment within a certain period, and the prospects for future business development. Sensitivity analysis is conducted to determine the extent to which changes in key variables affect the feasibility of the business. This study aims to analyze the financial feasibility of compost fertilizer enterprises managed by Village-Owned Enterprises (BUMDes) in Tebing Tinggi District, Tanjung Jabung Barat Regency, as well as to examine the business sensitivity toward key variables. The research method used is a survey method, with primary data obtained through interviews and questionnaires, and secondary data derived from BUMDes financial reports. Financial feasibility analysis was conducted using the criteria of Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP). The results of the study indicate that the compost fertilizer businesses operated by the four BUMDes Karya Bersama, Sumber Rezeki, Gerbang Nusantara, and Mandiri Sejahtera are financially feasible. This is shown by the positive NPV values of Rp 1,068,698,769 (Karya Bersama), Rp 458,576,404 (Sumber Rezeki), Rp 272,435,240 (Gerbang Nusantara), and Rp 302,157,163 (Mandiri Sejahtera); Net B/C ratios greater than 1 (3.67, 10.17, 7.81, and 7.71 respectively); and IRR values far above the discount rate of 7% (86%, 248%, 190%, and 187%). The sensitivity analysis revealed that business feasibility is highly influenced by changes in selling price, production cost, and sales volume. BUMDes with larger production capacities tend to achieve higher fixed-cost efficiency per unit compared to those with smaller capacities.